Parmenides’ following the path of Truth - Woszczyk, Agnieszka (Folia Philosophica, 2009)
Review of Dariusz Kubok's book: Truth and Opinions. A Study of the Philosophy of Parmenides of Elea. Katowice: University of Silesia Press, 2004.